2017
DOI: 10.1093/mnras/stx061
|View full text |Cite
|
Sign up to set email alerts
|

Gauge Choice in Conformal Gravity

Abstract: In a recent paper (MNRAS 458, 4122 (2016)) K. Horne examined the effect of a conformally coupled scalar field (referred to as Higgs field) on the Mannheim-Kazanas metric g µν , i.e. the static spherically symmetric metric within the context of conformal gravity (CG), and studied its effect on the rotation curves of galaxies. He showed that for a Higgs field of the form S(r) = S 0 a/(r + a), where a is a radial length scale, the equivalent Higgs-frame Mannheim-Kazanas metricg µν = Ω 2 g µν , with Ω = S(r)/S 0 ,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Several authors claimed that light deflection is problematic in CG, but possibly there is a way out [38,[49][50][51][52][53][54][55][56]. The work of Perlick and Xu [57] represented the major criticism on CG for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors claimed that light deflection is problematic in CG, but possibly there is a way out [38,[49][50][51][52][53][54][55][56]. The work of Perlick and Xu [57] represented the major criticism on CG for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…[31] pointed out that this term should be positive, so that it enhances the bending angle, in the same way that it provides an explanation of the flat galactic rotational curves in the absence of dark matter. This issue was settled [53,54] when it was shown that the sign of the linear term γr in the metric ( 6) can be reversed using a conformal transformation ds 2 → Ωds 2 followed by a coordinate transformation…”
Section: Mk Spacetimementioning
confidence: 99%